COVID-19, the direct relationship between capital, solidarity and lives. - Coelho Paraguassu, Eber (2020)
COVID-19 is imposing a radical change on humanity in the way of living and socializing. It is not little. It does not compare to other epidemics recently faced. No one in our generation or the generation of our parents or children had ever experienced a similar situation. We are confined. We are terrified of a virus, whose feats are not completely known.In Macapá, and certainly in other cities as well, sound cars circulate with messages that resemble films about dystopian futures: “stay at home, don't get contaminated, don't go out on the streets”. Images multiply of policemen forcing people to return home or of homeless people approaching passersby to plead for help.The streets are the public place par excellence. The space in which the recognition of the other becomes real, in which we see people who live realities different from ours, we practice empathy, we exercise our humanity. It is also the space where most of us put our bodies and souls for sale, in exchange for the remuneration that allows them to eat, dress and live. But public space is prohibited.In some cities in the south of the country, stone barricades prevent cars from accessing some places. The logic of the internal enemy, irresponsibly supported by the press and our leaders in recent years, is now enhanced by the concrete threat of the pandemic.There is something of hysteria and detachment from reality, be it in the terrorist speeches that lead people to stock up on food, buy medicine that does not fight the virus or make barricades, and in those inhabited by magical thoughts, for which nothing bad can happen. We are not facing a “little flu” as our dear president of the republic referred, but we are also far from facing a disease with a high virulent burden or high lethality.